Late and Chronic Antibody-Mediated Rejection: Main Barrier to Long Term Graft Survival - Qiquan Sun; Yang Yang (Clinical and Developmental Immunology)
Antibody-mediated rejection (AMR) is an important cause of graft loss after organ transplantation. It is caused by anti-donor-specific antibodies especially anti-HLA antibodies. C4d had been regarded as a diagnosis marker for AMR. Although most early AMR episodes can be successfully controlled or reversed, late and chronic AMR remains the leading cause of late graft loss. The strategies which work in early AMR have limited effect on late/chronic episodes. Here, we reviewed the lines of evidence that late/chronic AMR is the leading cause of late graft loss, characteristics of late AMR, and current strategies in managing late/chronic AMR. More effort should be put on the management of late/chronic AMR to make a better long term graft survival.